Phytopharmaceuticals: An Emerging Field for India's Herbal Tradition (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Phytopharmaceuticals represent a promising fusion of contemporary scientific advancements and traditional plant-based knowledge. These products are rooted in the centuries-old herbal medicine systems of Ayurveda, Siddha, Unani, Sowa-Rigpa, and Naturopathy in India. The country’s extensive ethnobotanical knowledge draws from the distinct therapeutic frameworks and bioactive insights provided by each of these traditions.Despite this rich heritage, challenges remain in terms of clinical validation, standardization, quality control, and regulatory compliance. Unlike traditional AYUSH substances, India's regulatory framework for phytopharmaceuticals is evolving to ensure their efficacy, safety, and international recognition. As the global demand for plant-based medications continues to rise, phytopharmaceuticals are increasingly viewed as safer alternatives for existing and emerging medical conditions.Advancements in AI-driven drug discovery, nanofabrication, and extraction technologies have accelerated the development of this field. Furthermore, regulatory reforms and mounting clinical evidence have established phytomedicine as a legitimate, evidence-based treatment option. Emerging trends highlight a shift toward ethical supply chains, sustainable sourcing, and personalized preventive healthcare.With growing global markets and a critical role in addressing public health challenges, such as antimicrobial resistance (AMR), phytopharmaceuticals are poised for transformative growth. India, with its dual strengths in pharmaceutical innovation and traditional medicine, is uniquely positioned to spearhead this global movement.